Breaking down the tumor immune infiltration within pediatric sarcomas - Weil, Rachel; Loeb, David (Frontiers in Endocrinology, 2023)
Immunotherapies are a promising therapeutic option, yet for a variety of reasons, these treatments have achieved limited success against sarcomas. The immunosuppressive tumor microenvironment (TME) of sarcomas as well as lack of predictive biomarkers, decreased T-cell clonal diversity, and abundant immunosuppressive infiltrating cells has thus far prevented major success using immunotherapies. Breaking down the TME into its individual components and understanding how the various cell types interact with each other, as well as in the context of the complex immune microenvironment, can provide insights into the development of effective immunotherapy treatments, potentially improving outcomes for those with metastatic disease.